2019
DOI: 10.14201/eks2019_20_a21
|View full text |Cite
|
Sign up to set email alerts
|

Comunidades virtuales: dinámicas emergentes de participación social y aprendizaje entre los jóvenes

Abstract: En el siguiente artículo se presentan los resultados de una investigación sobre el aprendizaje de los jóvenes mediante la participación social en comunidades virtuales. El proyecto se organizó en tres fases: (1) detección y cartografiado de entornos virtuales con alta participación de jóvenes de entre 15 y 29 años; (2) selección y estudio en profundidad de 7 comunidades virtuales; y (3) creación y distribución de un cuestionario en línea para calibrar la extensión del fenómeno. Se partió de un muestreo intenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…The results of the study confirm that virtual youth communities become an agent for inclusion of youth in participation in society (Puigcercos et al, 2019), strengthen the social participation of youth (Garcia-Galera et al, 2014). The data are consistent with a study (Krolo & Puzek, 2014) that revealed a permanent link between the use of social networks on the Internet and the number of members in nongovernmental organizations and civic engagement.…”
Section: Resultssupporting
confidence: 86%
“…The results of the study confirm that virtual youth communities become an agent for inclusion of youth in participation in society (Puigcercos et al, 2019), strengthen the social participation of youth (Garcia-Galera et al, 2014). The data are consistent with a study (Krolo & Puzek, 2014) that revealed a permanent link between the use of social networks on the Internet and the number of members in nongovernmental organizations and civic engagement.…”
Section: Resultssupporting
confidence: 86%
“…In the first phase, considering the characteristics of the problem addressed, the authors adopted a position close to the postulates of virtual (Hine, 2004) and multisited (Falzon, 2009) ethnography. This perspective allowed us to examine the digital idiosyncrasy of the countries studied, analysing more than one space at the same time, and simultaneously identify the connections between them (Morozov, 2018;Miño et al, 2019). Using virtual ethnography, we identified social and educational policies, along with models of digital governance and explored the emphasis that different states took when promoting digital citizenship, privacy, and security of Internet browsing (Raffaghelli, 2020).…”
Section: Methodological Designmentioning
confidence: 99%
“…Los videojuegos, el acceso a comunidades ESTUDIOS SOBRE EDUCACIÓN / 2021 online y el tiempo de dedicación están condicionados por el género. Lo cual genera un entorno privilegiado para ellos, ya que no solo implica una diferencia de oportunidades en clave de ocio, desarrollo personal e identitario y negociación del imaginario colectivo; sino que, de acuerdo con la investigación de Miño-Puigcercós et al (2019), en estos espacios se generan oportunidades de aprendizaje y desarrollo de la CD. ¿Qué sucede entonces con aquellos terrenos que no son explorados por la escuela?…”
Section: La Escuela En El Desarrollo De La Competencia Digitalunclassified